The bidder's curse - Lee, Young Han 1976-; Malmendier, Ulrike 1973- (Working paper series / National Bureau of Economic Research, 2007)
Traditional explanations for the popularity of auctions are efficiency and revenue maximization. We argue that auctions also induce 'overbidding,' i.e., bidding above the buyer's willingness to pay for an item outside the auction. Even if only few buyers overbid, they affect prices and allocations since auctions systematically pick those buyers as winners. We employ a novel approach to identify overbidding, using hand-collected data of eBay auctions with simultaneous fixed prices. We argue that fixed prices for identical items on the same webpage should provide an upper bound for bidders' willingness to pay in the auctions. In a first, detailed data set of board game auctions, we find that, in 42 percent of the auctions, the final price is higher than the simultaneous fixed price. The result is not explained by differences in item quality, shipping costs, or seller reputation. Auction experience, as measured by eBay's feedback score, does not eliminate overbidding. We also document that the large fraction of overbidding is induced by a small number of players: only 17 percent of bidders ever bid above the fixed price. The finding replicates in a broad cross-section of auctions (48 percent overbidding). Using a simple model of second-price auctions with a fixed price option, we show that transaction costs of switching between auctions and fixed prices are not sufficient to explain the results. Limited attention of bidders and utility of winning both contribute to explaining the empirical findings.